The Desirability of Zero Tolerance for Procrastination - Stephen Leeder (ACHSM, 2017)
I choose the desirability of zero tolerance for procrastination as my topic because I have seen so many opportunities lost in health and medicine because of delays in taking action. Procrastination ranks alongside shortage of cash as an explanation of things not being done. It is, quintessentially, bad management.